Central bank asset purchase programs in emerging market economies - John Beirne; Eric Sugandi (Asian Development Bank Institute (ADBI), 2023)
We investigate the impact of asset purchase programs (APPs) by 14 EME central banks during COVID-19, finding a statistically significant effect in compressing bond spreads vis-à-vis the US. A counterfactual analysis shows that in the absence of APPs, EME bond spreads would have been significantly higher. Country-specific VAR impulse response functions indicate that a shock imposed on asset purchases becomes persistent on bond spreads after around five to ten days, with a peak effect of around 40 basis points. Persistent stabilizing effects are also found on exchange rates and capital flow volatility, while stock markets and inflation expectations are overall not affected by the APPs.
Keywords: E44; E52; E58; 330; asset purchase program; quantitative easing; emerging market economies